The immunotherapy of Guillain-Barré syndrome (2018)
Introduction: Guillain-Barré syndrome is the most common cause of acute flaccid paralysis worldwide. Microorganisms such as Campylobacter jejuni, Cytomegalovirus, Epstein-Barr virus, Mycoplasma pneumoniae, Haemophilus influenzae and Zika virus have been linked to the disease. The most common clinical variants are acute inflammatory demyelinating polyneuropathy and acute motor axonal neuropathy. Plasma exchange and intravenous immunoglobulins are the standard therapy for the disease. Areas covered: research to elucidate the pathophysiology of Guillain-Barré syndrome has led to the development of drugs directed towards new potential therapeutic targets. This review offers a comprehensive view of the current treatment based upon the physiopathology. Expert opinion: patients with Guillain-Barré syndrome need a multidisciplinary approach, limitation to walk unaided and disability score are indicators for treatment as well as the presence of autonomic dysfunction and pain. Admission to intensive care units should be considered for those patients presenting with respiratory failure, bulbar involvement and progression of the disease. Research aimed to deciphering the pathophysiology of the disease, discovering new biomarkers and establishing algorithms of prediction of both the disease and its outcomes is warranted. © 2018, © 2018 Informa UK Limited, trading as Taylor and Francis Group.